(R)-ketamine as prophylactic and therapeutic drug for neurological disorders: Beyond depression. (August 2022) - Wang, Xingming; Yang, Jianjun; Hashimoto, Kenji
Abstract: Neurological disorders are the leading cause of disability and the second leading cause of death worldwide. The increasing social and economic burdens of neurological disorders are driven by global population growth and aging. Depression is a common psychiatric symptom in numerous neurological disorders. It is also a risk factor for Alzheimer's disease (AD) and other dementias, Parkinson's disease (PD), and stroke. The rapid-acting and sustained antidepressant actions of ( R, S )-ketamine for severe depression was accidentally discovered. Interestingly, ( R )-ketamine has greater potency and longer-lasting antidepressant-like effects than ( S )-ketamine in rodents. Importantly, its side effects in rodents and humans are lower than those of ( R, S )-ketamine and ( S )-ketamine. Furthermore, ( R )-ketamine could elicit beneficial actions in various rodent models of neurological disorders, including PD, multiple sclerosis (MS), and stroke. In this article, we review the potential of ( R )-ketamine as a prophylactic or therapeutic drug for neurological disorders including AD and other dementias, PD, MS, and stroke. Highlights: Depression is the most common psychiatric symptom in neurological disorders. Depression is a risk factor for dementia, Parkinson's disease, and stroke. Patients with multiple sclerosis have depression. Post-stroke depression is common in patients with stroke. ( R )-ketamine could be a prophylactic/therapeutic drug for neurological disorders.